Early Childhood Education and Ethnomathematics: A Study on the Emergence of Rationalities (Research, Society and Development, 2020)
This article aims to analyze the productivity of a learning situation entitled “The Earth as a Peppercorn”, made with the children of four and five years of a kindergarten. Based on a theoretical-methodological framework in the field of ethnomathematics, the study is part of a Master's dissertation. Methodologically, the qualitative research relied on ethnographic approaches. The research materials, analyzed through Discursive Textual Analysis, were composed of class recordings and material produced by the children. The results allowed the emergence of mathematical comparisons about distance, size and proportion of the stars.